2021
DOI: 10.1101/2021.03.31.21254518
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pharmacotherapy, drug-drug interactions and potentially inappropriate medication in depressive disorders

Abstract: Introduction: The aim of this study was to analyse prescription patterns and the determinants of drug-drug interactions (DDI) and potentially inappropriate medication (PIM) in pharmacotherapy of depressive disorders. Methods: Our study was part of a larger pharmacovigilance project funded by the German Innovation Funds. It included all inpatients with a main diagnosis in the group of depressive episodes (F32, ICD-10) or recurrent depressive disorders (F33) discharged from eight psychiatric hospitals in German… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…In accordance with the ethics approval, our retrospective study did not require individual patient consent. Previous publications from this research project that have used the same or similar datasets can be found in the reference list 24,26,29,36,38–40 …”
Section: Methodsmentioning
confidence: 99%
“…In accordance with the ethics approval, our retrospective study did not require individual patient consent. Previous publications from this research project that have used the same or similar datasets can be found in the reference list 24,26,29,36,38–40 …”
Section: Methodsmentioning
confidence: 99%
“…Regarding DDIs, polypharmacy is one of the most relevant risk factors (Johnell and Klarin, 2007;Wolff et al, 2021). The prevalence of clinically relevant DDIs among home-dwelling older adults reported in the scientific literature widely ranges from 35% to 77% (Novaes et al, 2017;Santos et al, 2017;Hermann et al, 2021;Sheikh-Taha and Asmar, 2021), and the most commonly reported are myopathy due to the increased levels of statins when used with calcium channel blockers and postural hypotension caused by the interaction between thiazide diuretics and ACE inhibitors (Sheikh-Taha and Asmar, 2021).…”
Section: The Clinical and Economic Impact Of Polypharmacymentioning
confidence: 99%
“…Prescription data from public health insurance providers in Germany show that outpatients were prescribed more than two billion daily defined doses (DDD) of psychotropic drugs in 2021, most of which were antidepressants (1.7 billion DDD, 79% of psychotropic drug prescriptions including tranquillizers, antipsychotics and antidepressants) (1). In a big retrospective study conducted in eight psychiatric hospitals in Germany including 14,418 inpatient cases, 31% of cases received at least five drugs simultaneously (polypharmacy) with a mean of 3.7 drugs daily (1.7 psychotropic drugs, 2.0 others) (2). In addition, due to the widespread anticholinergic properties of psychotropic drugs, especially antipsychotics (3)(4)(5), researchers have pointed out the need for interventions to reduce the prescription frequency of anticholinergic drugs and their assessment regarding their impact on clinical risks, especially in patients older than 65 years (6,7).…”
Section: Introductionmentioning
confidence: 99%